2005
DOI: 10.1091/mbc.e05-02-0148
|View full text |Cite
|
Sign up to set email alerts
|

An Anchor Site–Type Defect in Human Telomerase That Disrupts Telomere Length Maintenance and Cellular Immortalization

Abstract: Telomerase-mediated telomeric DNA synthesis is important for eukaryotic cell immortality. Telomerase adds tracts of short telomeric repeats to DNA substrates using a unique repeat addition form of processivity. It has been proposed that repeat addition processivity is partly regulated by a telomerase reverse transcriptase (TERT)-dependent anchor site; however, anchor site-mediating residues have not been identified in any TERT. We report the characterization of an N-terminal human TERT (hTERT) RNA interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 56 publications
5
60
1
1
Order By: Relevance
“…The requirement of residue R151 for interaction in our assay suggests that we are monitoring a different binding activity. We were unable to obtain a DNA binding affinity for the TEN domain using fluorescence anisotropy (data not shown), which is similar to results reported for both the Tetrahymena and human TEN domains using filter binding and electrophoretic mobility shift assays (Jacobs et al, 2006;Moriarty et al, 2005;Sealey et al, 2010). This result is not unexpected because a weak or rapid exchange between the DNA and the anchor-site would aid in translocation of the DNA substrate during telomeric synthesis.…”
Section: E76ksupporting
confidence: 67%
See 1 more Smart Citation
“…The requirement of residue R151 for interaction in our assay suggests that we are monitoring a different binding activity. We were unable to obtain a DNA binding affinity for the TEN domain using fluorescence anisotropy (data not shown), which is similar to results reported for both the Tetrahymena and human TEN domains using filter binding and electrophoretic mobility shift assays (Jacobs et al, 2006;Moriarty et al, 2005;Sealey et al, 2010). This result is not unexpected because a weak or rapid exchange between the DNA and the anchor-site would aid in translocation of the DNA substrate during telomeric synthesis.…”
Section: E76ksupporting
confidence: 67%
“…Assays of telomerase activity implicate an N-terminal domain of TERT [called telomerase essential N-terminus (TEN), GQ or Region I (Friedman and Cech, 1999;Jacobs et al, 2006;O'Connor et al, 2005;Xia et al, 2000)] in anchor-site function (Lue, 2004;Lue, 2005;Moriarty et al, 2005). Mutations within the Tetrahymena TEN domain decrease interaction with the DNA primer (Jacobs et al, 2006) and the primer can be photocrosslinked to a fragment containing the Tetrahymena and S. cerevisiae TEN domains (Lue, 2005;Romi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these results show that the N-DAT domain in mTERT, which is 82% similar to the human DAT region, functions properly in human cells (2). The N-DAT domain has been proposed to mediate telomerase access to telomeric chromatin (3,4) or to contribute to interactions between telomerase and telomere DNA repeats (40,52). Instead, our data identify the C terminus as a critical regulatory domain controlling the ability of TERT to stabilize telomeres in cells and to extend replicative lifespan.…”
Section: Discussionmentioning
confidence: 83%
“…These DAT (dissociates activities of telomerase) domains were proposed to be required for the recruitment of telomerase to telomeric chromatin (3,4). Other analyses of these TERT mutants found that the DAT mutants showed reduced processivity, principally on oligonucleotide primers matching the natural telomere sequence, indicating that the DAT regions contribute to interactions between TERT and its telomere substrate (40,52). These data suggest that the DAT mutants may fail to immortalize human cells because of impaired interaction with telomere DNA sequences or with telomeric chromatin.…”
mentioning
confidence: 99%
“…Studies have demonstrated that the human telomerase enzyme is one of the most processive telomerase complexes, especially compared to the murine one [10,11]. Human telomerase processivity is mediated by template and nontemplate regions of human TR (hTR) and by regions in human TERT (hTERT), specifically the C-terminal and N-terminal RNA interaction domain 1 [12][13][14][15][16][17]. The ectopic expression of hTERT enables the immortalization not only of human primary cells, but also of other primary vertebrate cells such as leporine, bovine, porcine, simian and cervine cells [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%